Youth driving change: Pastoralists join FAO’s Global Youth Dialogue on Sustainable Livestock Transformation, Rome - Spinelli, Madison (2023)
Empowering youth to actively engage in global dialogue on the future of livestock production systems is a fundamental principle of the CGIAR Research Initiative on Livestock and Climate. As a contribution to this, ILRI partnered with FAO to identify and support four pastoralist youth to attend the Global Youth Dialogue on Sustainable Livestock Transformation held in Rome from 25-27th September 2023, concurrently with the FAO Global Conference on Sustainable Livestock Transformation.